Design and Study the Reliability of a Stand-Alone Photovoltaic Energy System - ديب, ناظم (Latakia University Journal -Engineering Sciences Series, 2022)
The limitations of global resources of fossil and nuclear fuel, has necessitated an urgent search for alternative sources of energy. Therefore, a new way has to be found to balance the supply and demand without resorting to coal and gas fuelled generators. Environment safety has become very important for any energy system, Increasing demand of conventional sources has further increases the need and optimizes cost of non-conventional energy sources. Building a photovoltaic system is the process of designing, selecting and calculating the ratings of the equipment’s employed in the system. The process depends on a variety of factors such as geographic location, solar radiation, and load power requirements. The research presents a practical method for designing and simulating a Stand-Alone PV energy system using the PVsyst program to feed a household load in the city of Tartous. As well as determining the total energy flow across the entire system. The reliability of the PV system was calculated and the results showed the high reliability of the solar system, The reliability of the solar system after 20 years of the system's life was 0.99979.